Mom's Out: Employment after Childbirth and Firm-Level Responses - Francesca Carta; Alessandra Casarico; Marta De Philippis; Salvatore Lattanzio (Institute of Labor Economics (IZA), 2024)
This paper explores how firms respond to the exit of mothers from the labour market after childbirth. As an exogenous shifter in mothers' quits, we use a policy reform that extended the potential duration of unemployment benefits, which Italian mothers can receive also upon resigning within 12 months of giving birth. In response to the reform, we find that mothers have a higher probability of quitting in the first year after childbirth, a slightly decreased likelihood of being laid off, and a greater probability of remaining non-employed for at least 3 years following childbirth. Firms employing more exposed mothers respond by signicantly increasing net hiring and turnover, especially of young women. The surge in women's hiring primarily occurs through temporary contracts that are not converted into permanent ones, implying a persistent increase in the share of female temporary jobs. This outcome suggests the presence of statistical discrimination, manifesting through a decline in the quality of job opportunities available to women.
Keywords: J16; J23; J21; J38; J65; 330; quits; hirings; separations; unemployment benets; statistical discrimination; child penalty